Doing gender in Sweden's innovation policy, when transforming academic theory into regional practice - Malin Lindberg (European Regional Science Association (ERSA), 2010)
Since the establishment of the new governmental agency Vinnova in 2001 and the initiation of the regional growth agreements in 2000, the Swedish government has promoted innovation by means of regional innovation systems. Just as long, there has been a debate about the gendered aspects of these policy efforts, especially in relation to the transformation of academic theory into regional practice. In this paper, the matter of how gender is produced in Sweden's innovation policy is discussed in the light of a survey brought out on the pattern of prioritization among regional innovation systems in Sweden. The survey exposes how 75% of the regional innovation systems subject to public promotion via the Vinnväxt programme concerns groups of industries that primarily employ men. From a 'doing gender' perspective, this pattern implies that gender is done in a manner that distinguishes men from women in relation to regional innovation systems. A seed of change is to be seen, however, in the bottom up initiative to organize regional innovation systems around women's entrepreneurship and innovation, originating from the project Lyftet. In this paper, this seed of change is interpreted as an alternative to the segregating and hierarchical doing of gender in Sweden's innovation policy, introducing a way where it is unnecessary and undesirable to distinguish women from men when it comes to public promotion of regional innovation systems. Some final thoughts on how different measures of gender mainstreaming influence the doing of gender in the regional practice of innovation policy programs indicate that measures introduced ad hoc in already prioritized formations will not change the encompassing pattern of how different groups of industries are esteemed in the process of prioritization, thus leaving the predominant way of doing gender intact. However, a gleam of hope can be discerned in recent calls made by Vinnova on areas that bridge the gender segregated labour market, e.g. within innovation journalism, e-services and healthcare.
Keywords: 330